2018
DOI: 10.1111/iere.12320
|View full text |Cite
|
Sign up to set email alerts
|

Multilateral Trade Bargaining and Dominant Strategies

Abstract: Motivated by General Agreement on Tariffs and Trade bargaining behavior and renegotiation rules, we construct a three‐country, two‐good general‐equilibrium model of trade and examine multilateral tariff bargaining under the constraints of nondiscrimination and multilateral reciprocity. For a general representation of government preferences, we identify the bargaining outcomes that can be achieved using dominant strategy proposals for all countries. In our analysis, dominant strategy outcomes emerge when tariff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In subsequent work, Bagwell and Staiger (2010) consider rules under which efficient outcomes can be achieved in a subgame perfect equilibrium of a sequential bargaining game for the three-country model when transfers are allowed, the MFN rule is required, and other restrictions on bilateral negotiations, including rules regarding reciprocity and renegotiation, may be imposed. 2 Bagwell and Staiger (2016) develop the analysis in a different direction, by characterizing the outcomes that can be achieved in a multilateral bargaining setting in which any proposed outcome must satisfy the MFN rule along with the principle of multilateral reciprocity. As they show, in this "strong-rule" setting, countries are unable to alter the terms of trade, and as a consequence multilateral bargaining outcomes may be characterized while requiring only that countries make dominant-strategy proposals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent work, Bagwell and Staiger (2010) consider rules under which efficient outcomes can be achieved in a subgame perfect equilibrium of a sequential bargaining game for the three-country model when transfers are allowed, the MFN rule is required, and other restrictions on bilateral negotiations, including rules regarding reciprocity and renegotiation, may be imposed. 2 Bagwell and Staiger (2016) develop the analysis in a different direction, by characterizing the outcomes that can be achieved in a multilateral bargaining setting in which any proposed outcome must satisfy the MFN rule along with the principle of multilateral reciprocity. As they show, in this "strong-rule" setting, countries are unable to alter the terms of trade, and as a consequence multilateral bargaining outcomes may be characterized while requiring only that countries make dominant-strategy proposals.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, the Nash-in-Nash approach does not seem well-suited for a multilateral bargaining setting in which any proposed outcome must satisfy the MFN rule and the principle of multilateral reciprocity. As Bagwell and Staiger (2016) discuss, for a strong-rule setting wherein these requirements are strictly imposed, a home-country proposal for greater liberalization in one bilateral relationship is feasible only if the proposal calls for less liberalization in the other bilateral relationship.…”
Section: Introductionmentioning
confidence: 99%
“…In their working paper version, Bagwell, Staiger, and Yurukoglu (2018) showed that tariff bargaining under an MFN rule typically leads to inefficient outcomes that can exhibit either over‐ or under‐liberalization. See also Bagwell and Staiger (1999a, 2005, 2018) on the implications of different sets of rules for the outcomes of tariff bargaining.…”
mentioning
confidence: 99%
“… For a theoretical analysis of multilateral tariff negotiations when strict adherence to MFN and multilateral reciprocity is required, see Bagwell and Staiger (2018). …”
mentioning
confidence: 99%
See 1 more Smart Citation